Effectiveness of an Educational Program on High School Females Students’ Knowledge about Coronavirus Disease in Al-Diwanyia City - Sarra M. Agmoush, Aysin K. Noori, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective(s): A quasi-experimental design, using one group, test-retest approach, is employed to determine the effectiveness of education program on high school female students’ knowledge about coronavirus disease in Al-Diwanyia City from October10th 2021 to April 2nd 2022. Methodology: A non-probability, purposive sample of (30) high school female student, is selected for the purpose of the study. All subjects have signed consent form to present their agreement for participation in the study. The confidentiality of the data is also safeguard and they will be securely maintained during and after conducting the study. An education program and self-report questionnaire are constructed for the purpose of the study through review of related literature. The program is comprised of (4) lectures and the questionnaire is consisted of (2) main parts; the high school female students’ demographic characteristics and high school female students’ knowledge about coronavirus disease questionnaire. Content validity is determined for the education program and the study instrument through panel of experts and test-retest reliability is obtained for the study instrument in a pilot study. Data are gathered through the use of the study instrument as mean of data collection and analyzed through the application of descriptive statistical data analysis and inferential statistical data analysis approaches. Results: The study results depict that all high school female students’ knowledge about coronavirus disease has been improved as being exposed to the education program. Conclusion: The study concludes that the education program is confirmed to be an effective mean for improving high school female students’ knowledge about coronavirus disease. Recommendation: The study recommends that the education program can be utilized as an educational mean for enhancing the high school female students’ knowledge about coronavirus disease and further and a nation-wide research can be conducted with large sample size and wide-range scale of variables.